Global and gene-specific DNA methylation and hydroxymethylation in human skin exposed and not exposed to sun radiation - Mikaelly Batista da Silva; Alanne Rayssa da Silva Melo; Ludimila de Araújo Costa; Haline Barroso; Naila Francis Paulo de Oliveira (Sociedade Brasileira de Dermatologia, 2017)
Abstract: Background: epigenomes can be influenced by environmental factors leading to the development of diseases. Objective: To investigate the influence of sun exposure on global DNA methylation and hydroxymethylation status and at specific sites of the miR-9-1, miR-9-3 and MTHFR genes in skin samples of subjects with no history of skin diseases. Methods: Skin samples were obtained by punch on sun-exposed and sun-protected arm areas from 24 corpses of 16-89 years of age. Genomic DNA was extracted from skin samples that were ranked according to Fitzpatrick's criteria as light, moderate, and dark brown. Global DNA methylation and hydroxymethylation and DNA methylation analyses at specific sites were performed using ELISA and MSP, respectively. Results: No significant differences in global DNA methylation and hydroxymethylation levels were found among the skin areas, skin types, or age. However, gender-related differences were detected, where women showed higher methylation levels. Global DNA methylation levels were higher than hydroxymethylation levels, and the levels of these DNA modifications correlated in skin tissue. For specific sites, no differences among the areas were detected. Additional analyses showed no differences in the methylation status when age, gender, and skin type were considered; however, the methylation status of the miR-9-1 gene seems to be gender related. Study limitations: there was no separation of dermis and epidermis and low sample size. Conclusion: sun exposure does not induce changes in the DNA methylation and hydroxymethylation status or in miR-9-1, miR-9-3 and MTHFR genes for the studied skin types.